Turning the Switch: An Evaluation of the Minimum Wage in the German Electrical Trade Using Repeated Natural Experiments. Issue 3 (19th April 2013) - Boockmann, Bernhard; Krumm, Raimund; Neumann, Michael; Rattenhuber, Pia
Abstract: The introduction, abolition and subsequent re‐introduction of the minimum wage in the German electrical trade gave rise to series of natural experiments, which are used to study minimum wage effects. We find similar impacts in all three cases on wages, employment and the receipt of public welfare benefits. Average wages are raised by the minimum wage in East Germany, but there is almost no evidence for employment effects. The results also show that the wage effect is quickly undone after the abolition of the minimum wage.